In vitro study and characterization of doxorubicin-loaded magnetic nanoparticles modified with biodegradable copolymers. (17th February 2016) - Ebrahimi, Eommolbanin; Khandaghi, Amir Ahmad; Valipour, Fereshteh; Babaie, Soraia; Asghari, Fatemeh; Motaali, Soheila; Abbasi, Elham; Akbarzadeh, Abolfazl; Davaran, Soodabeh
Abstract : Magnetic nanoparticles are a main class of nanoscale materials with the potential to revolutionize present clinical therapeutic and diagnostic techniques. Functionalization of magnetic nanoparticles with copolymers, different surfactants, or other organic compounds is usually done in order to achieve better physicochemical properties. Poly (D, L-lactic-co-glycolic acid) (PLGA) polymers have been extensively used as biodegradable carriers for drug delivery. These biodegradable aliphatic polyesters, with proven biocompatibility, have versatile biodegradation properties, depending on their molecular weight and chemical composition. The aim of the present work was to assess the merits of Fe3 O4 -PLGA-PEG nanoparticles as anticancer drug carriers. For this purpose, magnetic Fe3 O4 nanoparticles were first prepared, and then the copolymer PLGA-PEG was synthesized with polyethylene glycol (PEG) of various molecular weights. The copolymer was conﬁrmed with Fourier transform infrared (FTIR) spectra. Doxorubicin was encapsulated within nanoparticles made of Fe3 O4 -PLGA-PEG, using the double emulsion method (w/o/w). The nanoparticles were characterized in terms of size, and the in vitro release of doxorubicin.